Faktor-Faktor Determinan Dismenorea Primer pada Remaja Putri di Sekolah Menengah Atas (SMA) Boarding School Aziziah Palembang: Determinant Factors of Primary Dysmenorrhea in Adolescent Girl in Aziziah Boarding School of Palembang - Octariyana Octariyana; Dian Lestari; Apriliani Apriliani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The prevalence of dysmenorrhea in Indonesia is 55% and 15%. Dysmenorrhea causes painful cramping in the lower abdomen, affecting adolescents' absenteeism from work and school activities by about 13-51%. It's perhaps influenced by age, menarche, body mass index (BMI), pain level, anemia, knowledge, weight, and height are associated with the incidence of dysmenorrhea. The purpose of this study was to determine the difference in age, menarche, mass index (BMI), pain level, HB levels, knowledge, weight, and height of students who experienced dysmenorrhea and non-dysmenorrhea and their relationship with dysmenorrhea in high school girls students of Aziziah boarding school Palembang. This research is a cross-sectional study. We collected 110 students who had met the inclusion criteria. The independent variables included knowledge, HB levels, levels, body mass index, height, and weight. The dependent variable was Primary Dysmenorrhea. Data were collected through interviews and observations. Statistical analysis using SPSS and tested by a non-parametric test method. The body mass index, pain level, and body weight of students in the primary dysmenorrhea group were significantly different compared to the primary dysmenorrhea group (p < 0.05). There is a significant relationship between body mass index, level, and weight of SMA Pondok Aziziah Palembang high school students with the incidence of primary dysmenorrhea, each with p = 0.01, p = 0.00, and p = 0.025. The body mass index (BMI), pain levels, and weight of girls students with dysmenorrhea were significant difference from non-dysmenorrhea, as well as a significant relationship with the incidence of dysmenorrhea in students at the Aziziah Boarding High School Palembang.